Prevalence of appetite level and quality of life among hospitalized elderly patients in medical and surgical wards at Hospital Universiti Sains malaysia (Hospital USM) - Hashim, Nur Hashamimi (Universiti Sains Malaysia, 2013)
Prevalence of poor appetite may reflect the functional activities and quality of life among elderly. Elderly need to have a better quality of life in order to continue their life without any barriers that could effects their performance in continuation of life events. The aim of this study was determines the association between level of appetite and quality of life among hospitalized elderly patients in Hospital USM. The total 100 respondents who were admitted in medical and surgical ward in Hospital USM were studied. Self administered questionnaire used in this study was Simple Nutritional Appetite Questionnaire (SNAQ) and WHOQOL-BREF, which were distributed by purposive sampling method. The data was analyzed by using Statistical Package for Social Science (SPSS) software version 20. By using Pearson Chi-Square Test and Fisher’s Exact Test, the finding showed no significant association between levels of appetite and quality of life among hospitalized elderly patients (p>0.950). Therefore, the overall results show the prevalence of poor appetite with moderate quality of life shows higher (75%) rather than good appetite (25%). As a conclusion, prevalence of poor appetite is higher in elderly patients. Thus, more study is needed to overcome the problem to improve their quality of life.